Development of crack meander protocol for fatigue resistance in stone mastic asphalt mixture using cellulose fibers - Radkeya, Sirous (2011)
One of the major distresses in asphalt pavement is fatigue cracking, which is caused by cyclic traffic loading. These cracks may begin as micro-cracks that grow, propagate, and combine into macro-cracks. The fatigue resistance of bituminous materials has been investigated in the laboratory using various fatigue test methods for many years. But the move for modeling the crack propagation during fatigue procedure has been recently started. This study was undertaken based on three objectives: first, to find out the rheological characteristics of cellulose oil palm fiber blended asphalt prior to use in Asphalt mixture. Investigating mechanical and chemical properties of cellulose oil palm fiber, physical properties of aggregate and asphalt binder were first stage of first objective followed by determination of optimum asphalt content (OAC). Blending asphalt binder with different percentages of cellulose oil palm fiber was also carried out as a part of first objective which completed by determination of rheological properties of blends and investigating behavior of blends (neat, RTFO aged and PAV aged) using Dynamic Shear Rheometer (DSR).The second objective was to evaluate the fatigue resistance of Stone Mastic Asphalt (SMA) with various proportions of cellulose fiber. Based on OAC obtained from first objective, twelve slabs (six slabs for beam samples and six slabs for cylindrical samples) were prepared using Turamesin for carrying out second objective. Four point beam fatigue test and indirect tensile fatigue test were used to investigate the effect of different percentages of cellulose fiber on fatigue life of SMA mixtures. It was found that adding 0.2 to 0.4 percent of cellulose fiber results best in fatigue performance of both asphalt binder and asphalt mixture. Evaluation the effect of different percentages of cellulose fiber in crack propagation and to correlate between cracks and fatigue resistance was defined as third objective. The main focus of third objective was to develop a crack meander protocol for the fatigue resistance of stone mastic asphalt mixture using cellulose fiber. As a part of third objective, a new computer program called Measurement and Mapping the Crack Meander (MMCM) was designed and developed. MMCM was aimed for measuring and mapping the cracks of SMA samples from beginning to the end of fatigue test. Based on the MMCM results and reports, the behavior of crack propagation was modeled and the resistance to crack propagation was evaluated by introducing Crack Propagation Rate (CPR) and Crack Area Development (CAD). Finally all the different mixtures (no fiber, 0.2% fiber, 0.4% fiber, 0.6% fiber, 0.8%fiber and 1.0% fiber) were ranked using direct comparison of CPR and CAD. In most cases PF0.2 showed the best resistance against crack propagation.